Conceptualizing handover strategies at change of shift in the emergency department: a grounded theory study - Tomolo Anne M; Lawrence Renée H; Garlisi Andy P; Aron David C (BMC, 2008)
Abstract Background The importance and complexity of handovers is well-established. Progress for intervening in the emergency department change of shift handovers may be hampered by lack of a conceptual framework. The objectives were to gain a better understanding of strategies used for change of shift handovers in an emergency care setting and to further expand current understanding and conceptualizations. Methods Observations, open-ended questions and interviews about handover strategies were collected at a Veteran's Health Administration Medical Center in the United States. All relevant staff in the emergency department was observed; 31 completed open-ended surveys; 10 completed in-depth interviews. The main variables of interest were strategies used for handovers at change of shift and obstacles to smooth handovers. Results Of 21 previously identified strategies, 8 were used consistently, 4 were never used, and 9 were used occasionally. Our data support ten additional strategies. Four agent types and 6 phases of the process were identified via grounded theory analysis. Six general themes or clusters emerged covering factors that intersect to define the degree of handover smoothness. Conclusion Including phases and agents in conceptualizations of handovers can help target interventions to improve patient safety. The conceptual model also clarifies unique handover considerations for the emergency department setting.